Preparation and Characterization of Dental Porcelain - Nurlaela Rauf (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2011)
Feldspar and quart from the local source is used as a base material for dental porcelain. The physical and chemical properties have been performed. The x-rays fluorescence is used to analyze the chemical composition. The composition of material and temperature preparation of dental porcelain contributes to shrink of burning and hardness, which is increased along with the increasing of treatment temperature.